Intoxications in the infanto-juvenile population cared for in an intoxication center in Northeast Brazil (Research, Society and Development, 2021)
The present study aimed to analyze intoxications in children and adolescents. This is a descriptive, retrospective study with a quantitative approach, carried out in a public tertiary hospital in the State of Ceará. The intoxication records of patients, suspected of acute poisoning by toxic agents, were evaluated in 2019. 959 records of patients aged